Fiscal Discipline and Exchange Rates : Does Politics Matter? - Jalles, Joao Tovar (IMF Working Papers; Working Paper ;, 2016)
We look at the effect of exchange rate regimes on fiscal discipline, taking into account the effect of underlying political conditions. We present a model where strong politics (defined as policymakers facing longer political horizon and higher cohesion) are associated with better fiscal performance, but fixed exchange rates may revert this result and lead to less fiscal discipline. We confirm these hypotheses through regression analysis performed on a panel sample covering 79 countries from 1975 to 2012. Our empirical results also show that the positive effect of strong politics on fiscal discipline is not enough to counter the negative impact of being at/moving to fixed exchange rates. Finally, we use the synthetic control method to illustrate how the transition from flexible to fully fixed exchange rate under the Euro impacted negatively fiscal discipline in European countries. Our results are robust to a number of important sensitivity checks, including different estimators, alternative proxies for fiscal discipline, and sub-sample analysis.